2023
DOI: 10.1042/bsr20220284
|View full text |Cite
|
Sign up to set email alerts
|

Impaired muscle stem cell function and abnormal myogenesis in acquired myopathies

Abstract: Skeletal muscle possesses a high plasticity and a remarkable regenerative capacity that relies mainly on muscle stem cells. Molecular and cellular components of the muscle stem cell niche, such as immune cells, play key roles to coordinate muscle stem cell function and to orchestrate muscle regeneration. An abnormal infiltration of immune cells and/or imbalance of pro- and anti-inflammatory cytokines could lead to muscle stem cell dysfunctions that could have long lasting effects on muscle function. Different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 250 publications
0
7
0
1
Order By: Relevance
“…Therefore, we believe that CNVs in the PLEC gene play an important role in regulating the growth traits and meat quality of LZBGs. This effect is primarily attributed to the multiple regulatory effects of PLEC on muscle development, as other researchers have demonstrated in previous studies [5,[44][45][46][47].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Therefore, we believe that CNVs in the PLEC gene play an important role in regulating the growth traits and meat quality of LZBGs. This effect is primarily attributed to the multiple regulatory effects of PLEC on muscle development, as other researchers have demonstrated in previous studies [5,[44][45][46][47].…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, PLEC prevents ubiquitination by stabilizing Dvl-2, thereby reducing the level of LC3-labeled Dvl-2 and antagonizing the autophagy system. The inhibition of autophagy results in incomplete skeletal muscle recovery and disrupts muscle regeneration [46,47]. In this study, the traits of body weight, chest circumference, carcass weight, and the cross-sectional area of the longissimus dorsi muscle were directly influenced by muscle mass, leading to significant differences in the means for these traits between the different CNV types.…”
Section: Discussionmentioning
confidence: 77%
“…Two studies showed that the proteasomedependent degradation of MyoD increased in muscle cells, and muscle loss developed with glucocorticoid treatment. 24,25 It was reported in another study that ubiquitin-proteasome-dependent myogenin levels decreased, and muscle atrophy occurred in dexamethasone-induced muscle cells. 26 Recent studies emphasize that calcineurin and mTOR inhibitors, which are other immunosuppressive agents used in patients, also cause muscle atrophy since it disrupts protein metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown in different studies that glucocorticoids can cause skeletal muscle loss by increasing or suppressing transcription factors such as MyoD and myogenin, which have an anabolic role in skeletal muscle differentiation, and Forkhead Box O (FOXO), which has a catabolic role. Two studies showed that the proteasome‐dependent degradation of MyoD increased in muscle cells, and muscle loss developed with glucocorticoid treatment 24,25 . It was reported in another study that ubiquitin‐proteasome‐dependent myogenin levels decreased, and muscle atrophy occurred in dexamethasone‐induced muscle cells 26 .…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 Diseases in which satellite cells are compromised by environmental factors can be added to this classification. 17 …”
Section: Introductionmentioning
confidence: 99%